2019
DOI: 10.1021/acsnano.9b01176
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent and Oriented Labeling of Gold Nanoprobes for the High-Resolution Tracking of a Single-Membrane Molecule

Abstract: Single-molecule tracking is a powerful method to study molecular dynamics in living systems including biological membranes. High-resolution single-molecule tracking requires a bright and stable signal, which has typically been facilitated by nanoparticles due to their superb optical properties. However, there are concerns about using a nanoparticle to label a single molecule because of its relatively large size and the possibility of cross-linking multiple target molecules, both of which could affect the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 61 publications
6
62
0
Order By: Relevance
“…In addition, because the localization precision now can approach the few-nm length scale, the influence of the GNP-to-ligand linker becomes of interest, in particular, its length and flexibilty, and how these might affect the accuracy in localization of the associated protein. Many of these questions are not fully answered, but recent studies have investigated these issues of multi-valent labeling and efforts to control it (Reina et al, 2018;Liao et al, 2019), as well as the influence of colloidal probe size (Ritchie et al, 2005;Clausen and Lagerholm, 2011;Etoc et al, 2018). In the case of the latter, the size of the probe may not have significant effects on diffusion within the cell as one would have initially assumed.…”
Section: Influence Of the Probementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because the localization precision now can approach the few-nm length scale, the influence of the GNP-to-ligand linker becomes of interest, in particular, its length and flexibilty, and how these might affect the accuracy in localization of the associated protein. Many of these questions are not fully answered, but recent studies have investigated these issues of multi-valent labeling and efforts to control it (Reina et al, 2018;Liao et al, 2019), as well as the influence of colloidal probe size (Ritchie et al, 2005;Clausen and Lagerholm, 2011;Etoc et al, 2018). In the case of the latter, the size of the probe may not have significant effects on diffusion within the cell as one would have initially assumed.…”
Section: Influence Of the Probementioning
confidence: 99%
“…Similarly, in previous work, we also found the use of 48 nm EGF-GNP probes seemingly did not impair the EGFR signaling pathway or uptake via clathrin-mediated endocytosis . To fully address this matter, one must systematically explore membrane diffusion for colloidal probes of differing sizes, as it has been recently demonstrated for synthetic membranes (Liao et al, 2019). Usage of smaller colloidal probes on the live cell membrane is challenging solely due to the dynamic speckle background which presents the biggest hurdle to overcome.…”
Section: Influence Of the Probementioning
confidence: 99%
“…Such studies typically report translational or rotational trajectories of nanoobjects bound to membranes via ligand-receptor interactions. The resulting trajectories can be rarely characterised as random walks, but are typically consistent with some type of anomalous diffusion in which the diffusion coefficient is time-dependent instead of constant [1][2][3][4][5][6][7][8][9]. This information can in principle serve as a readout of the molecular interactions between the object and the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Deducing the underlying molecular mechanisms * Electronic address: l.m.c.janssen@tue.nl, a.saric@ucl.ac.uk from the trajectories is highly non-trivial as a large number of possible molecular mechanisms can result in similar anomalous motility [10,11]. For instance, high-speed single-particle tracking studies have reported anomalous diffusion of functionalised nanoparticles, vesicles, and virus-like particles bound to receptors on membranes in living cells [1] and supported bilayers [2][3][4][5][6][7][8][9]. Various physical and chemical effects have been proposed to underlie the observed anomalous diffusion [12], including multivalent interactions between the nanoparticle and receptors, coupling between membrane leaflets [2], molecular pinning [2], receptor clustering [13], formation of transient membrane domains [14][15][16], and membranecytoskeleton interactions [17].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 For instance, high-speed single-particle tracking studies have reported anomalous diffusion of functionalised nanoparticles, vesicles, and virus-like particles bound to receptors on membranes in living cells 1 and supported bilayers. [2][3][4][5][6][7][8][9] Various physical and chemical effects have been proposed to underlie the observed anomalous diffusion, 12 including multivalent interactions between the nanoparticle and receptors, coupling between membrane leaflets, 2 molecular pinning, 2 receptor clustering, 13 formation of transient membrane domains, [14][15][16] and membranecytoskeleton interactions. 17 Here we take a reverse approach: we simulate physical interactions between a nanoobject and deformable fluctuating membranes and measure the resulting trajectories for membranes of various properties.…”
Section: Introductionmentioning
confidence: 99%